Gaya Kepemimpinan Kepala Desa Dalam Pelaksanaan Pemerintahan Desa Parsingguran II Kecamatan Pollung Kabupaten Humbang Hasundutan - Novita Lumban Gaol; Beby Masitho Batubara; Evi Yunita Kurniaty (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2023)
Leadership Style of the Village Head in the implementation of Village Government in Parsingguran II. Especially in leadership, the village head is still lacking in socializing, communicating and often making his own decisions so that the community does not participate in the village.study aims to determine the leadership style of village heads in village government. graduate ll. This study uses a descriptive qualitative method that provides a clear description of the problems studied by using the Kartono theory of leadership style six indicators of leadership style, namely the ability to make decisions, the ability to motivate, the ability to communicate, the ability to manage emotions, be responsible, the ability to control subordinates. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that the leadership style of the village head in village government is an authoritarian leadership style, this is because it focuses all decisions and policies taken from oneself. All division of duties and responsibilities is held by the authoritarian leader. While his subordinates only carry out the tasks that have been given. In an authoritarian leadership style, the leader controls all aspects of the activity. The leader gives what goals he wants to achieve, both major goals and minor goals.